2017
DOI: 10.1177/1464884917707121
|View full text |Cite
|
Sign up to set email alerts
|

Seizing the serendipitous moments: Coincidental creative processes in media work

Abstract: This article discusses the phenomenon of serendipity in media work and in media organizations. Based on an empirical analysis of diary material, we identify and elaborate three types of serendipitous processes in creative work, that is, serendipitous, semi-serendipitous and antiserendipitous processes. In addition, we discuss the role of lucky incidents and human capabilities in serendipity, and consider their value to creative processes in media organizations. We argue that conceptual frameworks and theories … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…There is interest in the exploration of serendipity in journalism, primarily in how news readers encounter information (Yadamsuren and Erdelez, 2010;Van Damme et al, 2014). However, Malmelin and Virta (2017) searched the journalism literature and found that serendipity has not been systematically researched in the area of journalism and media work, inspiring them to study how serendipity affects the story ideation process of journalists at a single magazine.…”
Section: Introductionmentioning
confidence: 99%
“…There is interest in the exploration of serendipity in journalism, primarily in how news readers encounter information (Yadamsuren and Erdelez, 2010;Van Damme et al, 2014). However, Malmelin and Virta (2017) searched the journalism literature and found that serendipity has not been systematically researched in the area of journalism and media work, inspiring them to study how serendipity affects the story ideation process of journalists at a single magazine.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of StumbleUpon, a now defunct web service that allowed users to browse a seemingly random series of webpages, Hauff and Houben (2012) explored how certain Wikipedia articles seem to serendipitously arrest users' attention more consistently than others. Scholars have also oriented serendipity toward forms of creative work, including Malmelin and Virta's (2019) investigation of serendipity within media organizations, where attention to "the accidental discovery of something valuable" (p. 1515) can support new and innovative production processes and content.…”
Section: The Three Princes Of Serendipmentioning
confidence: 99%
“…They maintained that, within journalism, a creative worker could be categorized as a person who benefits from a goal-driven personality, commercially oriented mind, and collaborative spirit. The other concept that may help our understanding of creative work in the media is "serendipity", as Malmelin and Virta (2019) contended. According to their study, media workers can develop and increase their creative skills by learning about serendipitous situations within their organizations that may stimulate their creative behaviors and ideas.…”
Section: Commonalitiesmentioning
confidence: 99%